Radiomics Based on Contrast-Enhanced MRI in Differentiation Between Fat-Poor Angiomyolipoma and Hepatocellular Carcinoma in Noncirrhotic Liver: A Multicenter Analysis - Zhao, Xiangtian; Zhou, Yukun; Zhang, Yuan; Han, Lujun; Mao, Li; Yu, Yizhou; Li, Xiuli; Zeng, Mengsu; Wang, Mingliang; Liu, Zaiyi (Frontiers in Oncology, 2021)
Objective To develop and externally validate a contrast-enhanced magnetic resonance imaging (CE-MRI) radiomics-based model for preoperative differentiation between fat-poor angiomyolipoma (fp-AML) and hepatocellular carcinoma (HCC) in patients with noncirrhotic livers, and to compare the diagnostic performance with that of two radiologists. Methods This retrospective study was performed with 165 patients with noncirrhotic livers from three medical centers. The dataset was divided into a training cohort (n=99), a time-independent internal validation cohort (n = 24) from one center and an external validation cohort (n=42) from the remained two centers. The volumes of interest (VOIs) were contoured on the arterial phase (AP) images, then registered to the venous phase (VP) and delayed phase (DP), and a total of 3396 radiomics features were extracted from the three phases. After the joint mutual information maximization feature selection procedure, four radiomics logistic regression classifiers including the AP model, VP model, DP model, and combined model were built. The area under the receiver operating characteristic curve (AUC), diagnostic accuracy, sensitivity, and specificity of each radiomics model and those of two radiologists were evaluated and compared. Results The AUCs of the combined model reached 0.789 (95%CI 0.579-0.999) in the internal validation cohort and 0.730 (95%CI 0.563-0.896) in the external validation cohort, higher than the AP model (AUCs, 0.711 and 0.638), and significantly higher than the VP model (AUCs, 0.594 and 0.610) and DP model (AUCs, 0.547 and 0.538). The diagnostic accuracy, sensitivity, and specificity of the combined model were 0.708, 0.625, and 0.750 in the internal validation cohort, and 0.619, 0.786, and 0.536 in the external validation cohort, respectively. The AUCs for the two radiologists were 0.656 and 0.594 in the internal validation cohort, and 0.643 and 0.500 in the external validation cohort. The AUCs of the combined model surpassed the two radiologists’ and were significantly higher than that of the junior one in both validation cohorts. Conclusions The proposed radiomics model based on triple-phase CE-MRI images was proven to be useful for differentiating between fp-AML and HCC, and yielded comparable or better performance than two radiologists in different centers, with different scanners and different scanning parameters.